School Environment as Barrier to Effective Academic Performance among Students with Physical Disabilities In Ilorin Metropolis - Famolu, Florence Bosede (Jurnal Kajian Bimbingan dan Konseling, 2023)
Insufficient infrastructural facilities make it difficult for a large number of students with visual and mobility impairment to walk around the campus and attend lectures. Also, fewer than ideal library facilities decrease the amount of study resources that are available to these students. This study investigated the school environment as barrier to effective academic performance among students with physical disabilities in the Ilorin metropolis, Kwara State. The descriptive survey of a correlational type was implemented using purposive sampling for this study. A purposive sampling technique was used to select 98 students in the Ilorin metropolis with physical disabilities, and the whole 98 students participated in this study. The population for the study comprised all secondary school students with physical disabilities in Ilorin metropolis, while 98 students with physical disabilities constituted a sample for the study. A research-designed questionnaire entitled: School Environment Scale was adapted for this study. For academic performance, the academic results of students with physical disabilities in the two core subjects were collected from the school authorities. The data collected were analyzed using percentage for demographic data and research questions, while the null hypothesis formulated were tested at 0.05 level of significance using regression. The findings revealed that most students with physical disabilities had difficulty accessing various areas in the school environment and, as a result, served as a barrier to their effective academic performance. Moreover, an F- value of 4.14 with a p-value of .045 is less than 0.05 significant level. Since the calculated p-value is less than the significant level, the null hypothesis one is rejected. Thus, the school environment significantly hinders effective academic performance among students with physical disabilities in the Ilorin metropolis. Finding also shows that academic performance has a Beta weight (β) of -0.208, t equal to 2.036, p greater than 0.05. Based on the result, it could be seen that poor academic performance among students with physical disabilities has a significant relationship with the school environment. Based on the findings, it was recommended that school owners should structure their school environment so that students with physical disabilities will have easy access to different facilities. There is a need for School Counsellors to organize group and individual counseling services for students with physical disabilities to expose them to good study habits in order to achieve success academically